Enhancing English Teachers’ Vocabulary Instruction and Speaking Assessment Competence through MGMP Training in Pekanbaru - Resy Oktadela; Putri Octa Hadiyanti; Estika Satriani; Wira Jaya Hartono; Niken Fatricia; Yusti Elida (Journal of English Language and Education, 2026)
Continuous improvement of instructional competency among in-service English teachers constitutes a strategic imperative in advancing the caliber of language education at the secondary level. Grounded in a community service research framework, this study investigates the delivery and outcomes of a structured vocabulary teaching training program organized through the MGMP network for Senior High School English teachers in the city of Pekanbaru, Riau Province. The training was conducted on Saturday, 6 June 2026, at SMA Negeri 8 Pekanbaru. The overarching goal was to examine whether participation in this training produced measurable gains in teachers' capacity to implement vocabulary instruction that supports the development and assessment of students' oral communicative performance. A pre-experimental one-group pre-test and post-test design was employed, engaging 32 teachers drawn from various Senior High Schools across the city of Pekanbaru. Multiple data sources were utilized, comprising a validated knowledge assessment instrument (Cronbach's α = 0.87), structured classroom observation checklists, and individual semi-structured interviews. Statistical analysis revealed a substantial mean improvement of 23.38 points between pre- and post-training assessments (t(31) = 14.67, p 0.001; Cohen's d = 1.94). Observational records indicated that the majority of participants (87.5%) successfully transitioned from isolated vocabulary drills toward the integration of lexical learning within task-based oral communication activities. Thematic patterns extracted from interview responses highlighted three salient dimensions of professional growth: heightened instructional self-efficacy, expanded assessment design capability, and greater congruence between training content and pedagogical practice. These results underscore the value of institutionalizing vocabulary-focused pedagogical training within MGMP structures as an enduring mechanism for elevating English language teacher professionalism in the regional context.